Merdeka Belajar Kampus Merdeka (MBKM): Evaluasi Implementasi dan Dampaknya terhadap Kesiapan Kerja Mahasiswa - Cahya Adrevi; Sujarwo; Desy Safitri (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The Merdeka Belajar Kampus Merdeka (MBKM) program was developed by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia as a step towards modernizing higher education and bridging the gap between the academic world and the workforce. Although it has been widely adopted in various universities, the efficiency of this program in enhancing students’ job readiness remains a key question. The aim of this research is to evaluate the implementation of the MBKM program and its impact on students’ job preparation, including both soft skills and hard skills. The background of the issue reveals a gap between higher education graduates’ competencies and the needs of the workforce, which has driven the government to initiate the MBKM policy as a solution to better prepare students for the dynamics of the labor market. The research problem focuses on the effectiveness of MBKM program implementation across various universities and how it affects students’ job readiness. Through a comprehensive literature review method, this study analyzes various scientific publications, policy reports, and evaluation studies related to MBKM from 2020 to 2024. The findings indicate that the implementation of MBKM still varies across higher education institutions with several challenges, such as infrastructure readiness, administrative systems, and stakeholder understanding. However, a positive correlation was found between student participation in the MBKM program, particularly in industry internships and collaborative projects, and improvements in adaptability, problem-solving skills, and technical competencies needed in the workforce. The novelty of this research lies in the comprehensive mapping of critical factors in the implementation of MBKM as well as the development of a sustainable evaluation framework that universities can use to enhance the effectiveness of the MBKM program in preparing graduates who are job-ready and globally competitive.